The impact of intestinal microbiota in antithymocyte globulin–based myeloablative allogeneic hematopoietic cell transplantation. Issue 7 (25th January 2022) - Gu, Zhenyang; Xiong, Qian; Wang, Lu; Wang, Lili; Li, Fei; Hou, Cheng; Dou, Liping; Zhu, Baoli; Liu, Daihong
Abstract : BACKGROUND: The correlation between intestinal microbiota and clinical outcomes after allogeneic hematopoietic stem cell transplantation (allo‐HCT) has been reported in platforms with T‐cell depletion or postcyclophosphamide‐based graft‐vs‐host disease (GVHD) prophylaxis regimens. It is still unclear whether it is the same in platforms of antithymocyte globulin (ATG)–based myeloablative allo‐HCT. METHODS: A total of 603 fecal specimens from 100 consecutive patients receiving allo‐HCT were collected between December 2018 and July 2020. Fetal samples were profiled with next‐generation sequencing of bacterial 16S ribosomal RNA (rRNA) genes. RESULTS: The diversity decreased to the lowest level at approximately day 12 after allo‐HCT and then increased over time. According to the diversity of 314 samples that were collected from 86 patients during the engraftment period, patients were grouped into the low‐ and high‐diversity groups. Two‐year overall survival in the high‐diversity group was significantly longer than that in the low‐diversity group (83.7% vs 60.6%, P = .026). Further analysis revealed that worse outcomes for patients with low diversity were associated with increased risk of worse outcomes for patients with low diversity (adjusted hazard ratio, 4.95; P = .046). Its association with relapse and GVHD was not found. Compositional analysis of fecal microbiota revealed that the abundance of bacteroides decreased greatly during allo‐HCT, whereas that of Enterococcus, Klebsiella, and Escherichia was found to be increased. CONCLUSIONS: This study indicates that gut dysbiosis in platforms of ATG‐based myeloablative allo‐HCT featured loss of bacterial diversity. The diversity of the intestinal flora at the engraftment period was an independent predictor of longer survival. LAY SUMMARY: The correlation between intestinal microbiota and clinical outcomes after allogeneic hematopoietic stem cell transplantation (allo‐HCT) is reported in platforms with T‐cell depletion or postcyclophosphamide‐based graft‐vs‐host disease (GVHD) prophylaxis regimens. It is still unclear whether it is the same pattern in platforms of antithymocyte globulin (ATG)–based T‐cell repletion myeloablative allo‐HCT. Our study indicated that gut dysbiosis in platforms of ATG‐based myeloablative allo‐HCT also features loss of bacterial diversity. The diversity of the intestinal flora at the engraftment period is an independent predictor of longer survival. Abstract : Gut dysbiosis in platforms of antithymocyte globulin–based myeloablative allogeneic hematopoietic stem cell transplantation featured loss of bacterial diversity. The diversity of the intestinal flora at the engraftment period was an independent predictor of longer survival.